Effects Of Mitsuokella Jalaludinii And Lactobacillus Cultures Supplementation On The Performance And Nutrient Utilization Of Broiler Chickens - Lee, Hooi Ching (2002)
A study on the preservation techniques of Lactobacillus cultures was conducted by freeze-drying the cultures in different formulations of protectants and storage at -20°C, 4°C and room temperature for 1 to 6 months. Among the six formulations used, cultures preserved with 10% sucrose or 10% skim milk remained unchanged in their viability after freezing and after freeze-drying. All the freeze-dried formulations showed no viability losses after I month and 6 months of storage at _20° C, while a little loss at 4°C after 6 months of storage was observed. The viability in all the formulations was reduced after I month of storage at room temperature, in particular cultures stored in 10% skim milk. There was no viable count for all the formulations at 10-1 dilution, except for samples stored in 10% sucrose (6 x 103 CFU/ml) after 6 months of storage at room temperature. A feeding trial using 480 one-day-old broiler chicks and eight diets was conducted tor 6 weeks. The diets were designed to determine the effects of Mitsuokellajalaludinii (a new phytase-producing bacterial species) and Lactobacillus cultures (as probiotics) on minerals (Ca, P, Zn, Cu and Mn) and nitrogen utilization, and growth performance of